Structural origin for the strain rate dependence of mechanical response of fluoroelastomer F2314. Issue 10 (27th March 2019) - Chang, Jiarui; Lin, Yuanfei; Chen, Wei; Tian, Fucheng; Chen, Pinzhang; Zhao, Jingyun; Li, Liangbin
ABSTRACT: The structural evolution of fluoroelastomer F2314 is studied during uniaxial tensile in a large strain rate range (0.1–150 s −1 ) with the combination of a homemade high‐speed stretching device and in situ small‐ and wide‐angle X‐ray scattering techniques. Based on the mechanical behaviors and structural evolutions, three strain rate regions (I–III) are defined. The microphase‐separated structure plays an important role in the mechanical response of F2314. In Region I, deformation of soft domains is the main process before yielding, accompanied by the destruction of lamellar crystals in hard domains. In the stress plateau zone, deformation of hard domains is confirmed as the primary mechanism of energy dissipation. With the orientation parameter of the amorphous phase reaching a critical value, strain hardening is triggered. Recrystallization also takes place in strain hardening zone. In Region II, due to the mismatch between the mobility of molecular chains in hard domains and the acting time of stress, large deformation of hard domains is more and more difficult to occur with the disappearance of recrystallization. In Region III, as almost all molecular chains have no time to adjust or relax to fit the stress field, the sample presents a brittle fracture. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 607–620 Abstract : The structural evolution of fluoroelastomer F2314 during uniaxial tensile is studied in a large strain rate range (0.1–150 s −1 ) with the combination of a homemade high‐speed stretching device and in situ small‐ and wide‐angle X‐ray scattering techniques. With a time resolution of 2 ms, the structural origin for the strain rate dependence of mechanical response is revealed. The microphase‐separated structure is found to play an important role.